Interpretation of the surface electromyogram in dynamic contractions - Farina, D. (Exercise and Sport Sciences Reviews, 2006)
This review focuses on methods for extracting information from the surface EMG recorded in dynamic contractions. It examines the techniques, requirements, and limitations associated with detecting the timing of muscle activation, assessing the modulation of signal amplitude, performing EMG spectral analysis, and estimating conduction velocity. The conclusion is that interpretation of the surface EMG in dynamic tasks requires caution.